Návrh na optimalizaci mzdových nákladů podniku - Nečas, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Bakalářská práce je zaměřena na optimalizaci mzdových nákladů konkrétního podniku. Cílem práce je pomocí různých ukazatelů identifikovat nedostatky a rezervy ve mzdových nákladech a na tomto základě navrhnout opatření na zlepšení mzdových nákladů podniku.

This bachelor's thesis is concentrated on the optimization of wage costs of an concrete enterprise. The objectives of the work are to identify imperfections and drawbacks in wage costs with help of various indicators and on the basis of this to suggest appropriate recommendations on how to improve wage costs of the Enterprise.
The Proposal of Wage Optimization for Entreprise
Keywords: Mzdové náklady; náklady práce; mzdy; mzdový systém; ukazatelé produktivity.; Wage Cost; Labour Cost; Wages; Wage Payment Plan; Productivity Index.